The ‘scorecard’ and ‘kubotereka’ spatial orders : a comparative study of mine housing strategies at Amandelbult (South Africa) and Unki (Zimbabwe) platinum mines - Bezuidenhout, Andries (University of Pretoria, 2022)
Thesis (PhD (Sociology))--University of Pretoria, 2022.